2010
DOI: 10.1016/j.ijmm.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage endolysins: A novel anti-infective to control Gram-positive pathogens

Abstract: Endolysins (or lysins) are highly evolved enzymes produced by bacteriophage (phage for short) to digest the bacterial cell wall for phage progeny release. In Gram-positive bacteria, small quantities of purified recombinant lysin added externally results in immediate lysis causing log-fold death of the target bacterium. Lysins have been used successfully in a variety of animal models to control pathogenic antibiotic-resistant bacteria found on mucosal surfaces and infected tissues. Their specificity for the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
316
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(323 citation statements)
references
References 56 publications
4
316
0
3
Order By: Relevance
“…The absence of bacterial resistance against lysin is considered as a major advantage of using phage lysins (Fischetti 2010), as the bacterial cell would have to modify the structure of its cell wall to avoid enzymatic action. It was found that exposing bacteria to a particular lysin for 40 reproductive cycles did not give any resistant strains (Fischetti 2010).…”
Section: Application Of Phage Lysin In Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of bacterial resistance against lysin is considered as a major advantage of using phage lysins (Fischetti 2010), as the bacterial cell would have to modify the structure of its cell wall to avoid enzymatic action. It was found that exposing bacteria to a particular lysin for 40 reproductive cycles did not give any resistant strains (Fischetti 2010).…”
Section: Application Of Phage Lysin In Foodmentioning
confidence: 99%
“…It was found that exposing bacteria to a particular lysin for 40 reproductive cycles did not give any resistant strains (Fischetti 2010). However, the production of lysin is expensive and, moreover, they are relatively unstable large proteins that are prone to proteolysis and lose its activity in some foods (Coffey et al 2010).…”
Section: Application Of Phage Lysin In Foodmentioning
confidence: 99%
“…Bacteriophages infecting Gram-positive bacteria harbour endolysins that are modular in nature, and contain at least one catalytic and one CBD (Fischetti, 2005(Fischetti, , 2010Sudiarta et al, 2010). However, endolysins of phages infecting Gram-negative bacteria contain only a catalytic domain (Cheng et al, 1994).…”
Section: Regulation By Specificitymentioning
confidence: 99%
“…Bacteriophages are able to infect and lyse bacterial cells, and it is this feature that makes them important antimicrobial agents (Sulakvelidze et al, 2001;Hermoso et al, 2007), especially because of the rapid emergence of multidrug-resistant bacteria (Loeffler et al, 2001;Schuch et al, 2002;O'Flaherty et al, 2009;Fischetti, 2010). Bacteriophages use two independent mechanisms to lyse host cells.…”
Section: Introductionmentioning
confidence: 99%
“…23 Unique endolysins that kill bacteria could play a major role in human and animal health and in food safety. 24 This list goes on.…”
Section: Student Discoveries Must Be Significant and Continue To Be Umentioning
confidence: 99%